2009
DOI: 10.3122/jabfm.2009.05.080155
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Edinburgh Postnatal Depression Scale (EPDS) and Patient Health Questionnaire (PHQ-9) to Assess Increased Risk of Depression among Postpartum Women

Abstract: Objectives:To compare the Edinburgh Postnatal Depression Scale (EPDS) and Patient Health Questionnaire (PHQ-9) as screening tools for postpartum depression.Methods: This study population included the first 500 women to enroll and return their packets during an ongoing study of postpartum depression.Results: The primary outcome of this study was to find rates of concordance and discordance in the EPDS and PHQ-9 categories of "normal" and "increased risk for major depressive disorder." Overall, 97% of eligible w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 46 publications
4
57
2
2
Order By: Relevance
“…The involvement of each practice lasts for approximately 36 months. 11 Human subjects training was required for all practice personnel who would be involved in the patient consent process, as well as for the lead study physician and nurse coordinator from each site. The required training varied by site and in many instances was specified by the site's IRB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of each practice lasts for approximately 36 months. 11 Human subjects training was required for all practice personnel who would be involved in the patient consent process, as well as for the lead study physician and nurse coordinator from each site. The required training varied by site and in many instances was specified by the site's IRB.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] These issues include obtaining approval for sites that are not affiliated with a local or regional IRB, 1 the need to obtain approvals from multiple site-specific IRBs, 1,3,4,6 the variation in requirements for submission and local rules for study assessments among multiple IRBs, and requirements for varying types of human subject training. 11 Solutions have been recommended and adopted for many of these issues. 1,2,10,12 For example, central IRBs that review and approve PBRN protocols on behalf of multiple sites and other IRBs have been proposed and tested with at least limited success.…”
mentioning
confidence: 99%
“…Although one small study (n ¼ 13 depressed women) found the PHQ-9 to be less accurate than the EPDS or Postpartum Depression Screening Scale (PDSS), 6 the remaining three studies found the PHQ-9 to be sensitive and specific in identifying PPD, 7 better than or at least comparable to the EPDS. 8,9 Therefore, it appears that the PHQ-9, which was used in the present study, may be a valuable tool for studying PPD prevalence.…”
mentioning
confidence: 99%
“…Despite the variety of topics and varying study designs, many of the same implementation strategies and support techniques proved to be useful across studies. Each of the studies introduced a practice change: using spirometry to evaluate patients with asthma and chronic obstructive pulmonary disorder 20 ; introducing screening, diagnosis, and management support for postpartum depression [21][22][23][24] ; using new asthma tools (asthma APGAR tools) in managing children and adults with asthma 25 ; and assessing the effect of 2 classes of long-acting bronchodilators on exacerbation rates in black adults with asthma.…”
Section: Methodsmentioning
confidence: 99%